O transconstitucionalismo na jurisprudência do tribunal pleno do Supremo Tribunal Federal: o diálogo entre ordens jurídicas distintas como mecanismo de motivação e fortalecimentodas decisões que versam sobre direitos fundamentais proferidas entre 2010 e 2017. - Gonçalves, Bruno José Pedrosa de Arruda (2018)
Throughout human history, human beings has always desired to know not only the people in their society, but all people around the world. In this globalized context, and with the rise of a "global society," the national law has been insufficient to solve constitutional issues. Therefore, rights from different legal orders have emerged; such as local, supranational, regional, international, transnational etc. This has created the perfect setting for the transconstitutionalism debate. Through this study it will be shown that the dialogue between the Supreme Court (STF) and the Inter-American Court of Human Rights provides an encouraging mechanism for the fundamental rights verdicts.